HISTORY OF THE JUDICIAL SYSTEM OF KASHKADARYA REGION (20s of the 20th Century) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article also discusses the features of the judicial system of the Soviet era and their impact on public life.